Students as targeted prospects for money mule / Mohd Shafiz Saharan, Mohd Fazil Jamaludin and Khairul Azfar Adzahar - Saharan, Mohd Shafiz (Universiti Teknologi MARA, Kedah, 2023)
Money mule has become a major headline in the news and a rising phenomenon trapping innocent people into a criminal syndicate. A money mule is a fraud and criminal activity that takes advantage of the emerging technology and digital platform developed by financial institutions (Alin, 2022). The uprising technology has come with a threat to the financial economy and brought bigger damage to the victims in terms of legal charges by the authorities. Money mules use their bank accounts to receive illegal currency, money taken through a swindle, purposefully or unintentionally (Hulsse & Hiulsse, 2017). Money mule works as part of a criminal network to hire individuals as money mules whose bank accounts and all private information about the account will be used for money laundering (Saharan et al., 2022). The purpose is to diversify the trails to avoid the authorities’ detection. The money received by the money mule will be wired to the thirdparty account and will receive a commission from the transaction. The money mules also open up an account for this purpose, making them accomplices in money laundering (Richet, 2013). Therefore, the authorities have made money mules a prime concern due to the growing number of cases and have taken the necessary prevention measures to ensure a stricter financial process. Recently, students are becoming easy targets for the money mule syndicate. According to a study conducted by (Cifas, 2021), this is a fact that can be demonstrated. The study found that in the year 2020 alone, there were 17,157 suspected incidents of money muling activity involving individuals aged between 21 and 30 years old, which is a 5% rise from the year 2019. In 2021, they were 29,769 bank accounts were found to be money mule accounts (Yong, 2022). Police department has started 29 investigations into the conduct of "account mules" resulting in a loss of RM2.82 million between January 1 and February 20 of this year (Maszureen, 2023). This happened due to the attractive financial rewards offering an abundance of perks promised to them (Vedamanikam & Chethiyar, 2020). Literature shows that most money mules are young people who lack prior knowledge of the hidden criminal operation behind the job. In addition, unemployed persons, students, and those in financial difficulty are easy targets for criminals, according to Europol (2022). Persons aged 15 to 44 appear to actively participate in financial crime, with individuals aged 24 to 34 having the highest participation (Leukfeldt & Jansen, 2016). The student has become an easy target due to several factors like an attractive financial reward and work flexibility besides being unaware of the hidden criminal job. In these challenging economic situations, students are also affected by the rising cost of living and other related expenses (Alin, 2022). However, peer and lifestyle pressure can also contribute to this matter. Hence, it is found that they have become an easy target due to these financial needs. When they get job offers, they tend to be impulsive and randomly accept the offer (Leukfeldt & Kleemans, 2019), seeing it as a hard-to-lose opportunity. According to the poll, nearly one in ten (9%) 18 to 24-year-olds would agree to move money via their bank accounts for a fee (Pedro, 2022).